The Influence of Transformational Leadership Style on the Performance of Posyandu Cadres in Labae Village - Suhairi Suhairi; Andi wilda yanti; Andi Riska Rahmadani; Puji Rahmah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
Posyandu cadres play a strategic role in supporting basic community health services, particularly for mothers and toddlers. However, the success of Posyandu activities is highly influenced by the quality of leadership implemented by the Posyandu manager or coordinator at the village level. This study aims to analyze the influence of transformational leadership style on the performance of Posyandu cadres in Labae Village. This research employs a quantitative approach using a survey method. The population of this study consists of all 45 Posyandu cadres in Labae Village; therefore, the sampling technique used is total sampling (census sampling). Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using simple linear regression and a partial test (t-test) with the assistance of SPSS software. The results indicate that transformational leadership style has a positive and significant effect on the performance of Posyandu cadres, with a significance value of less than 0.05. These findings demonstrate that leadership characterized by inspirational motivation, intellectual stimulation, and individualized consideration can enhance the responsibility, discipline, and service quality of Posyandu cadres